2016
DOI: 10.1097/pcc.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of α2-Agonists for Sedation in Pediatric Critical Care

Abstract: Reporting of study results using the outcome "time maintained at target sedation score' for clonidine or dexmedetomidine was poor. Only one trial compared clonidine with midazolam using a sedation score outcome. This study was underpowered to demonstrate equivalence to midazolam as a sedative. The adjunctive use of clonidine demonstrated significant decreases in opioid use in neonates but not in older groups. Clonidine dose was inconsistent between studies. Dexmedetomidine demonstrated an opioid-sparing effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 27 publications
0
43
0
1
Order By: Relevance
“…However, in recent years an increase of studies about the use of alpha-agonists has been seen, as shown in the systematic review published in the literature recently [15]. The data are very heterogeneous, which prevents getting good conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years an increase of studies about the use of alpha-agonists has been seen, as shown in the systematic review published in the literature recently [15]. The data are very heterogeneous, which prevents getting good conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The α 2 agonists have been of intense interest in the pediatric critical care literature as sedative agents . An alternative mechanism of action to opioids and benzodiazepines makes them attractive to clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Bioavailability of orally administered clonidine formulations has been estimated to be approximately 55% in children . Pediatric‐derived information to date, on both α 2 agonists, has been scarce with limited evidence of efficacy on sedation outcomes …”
Section: Introductionmentioning
confidence: 99%
“…One recent systematic review on the efficacy of alpha-2 agonists for sedation in the pediatric critically ill population included three RCTs using clonidine, but did not pool estimates. They concluded that robust evidence was lacking for the use of clonidine as a sedative in the pediatric critically ill population [14]. A Cochrane meta-analysis that assessed the efficacy of alpha-2 agonists on the quality of sedation in ventilated critically ill patients did not include any studies on clonidine [15].…”
Section: Introductionmentioning
confidence: 99%